Forbidden In Surat Al-Hujurat Is a Semantic Grammatical Study - Khorsheed Kareem, Affan; Muhi Rebat, Shaymaa (International Journal of Psychosocial Rehabilitation, 2020)
Forbidding is a linguistic method in the Arabic language that is intended to leave doing the thing and avoiding it and avoiding it, for what is left is forbidden and it is presented in various structures in the linguistic context, either explicitly or implicitly, and a linguistic reference, especially the grammatical one, is not free from it, but the author took this method - the prohibition - by urging the study and statement of grammatical aspects and rulings, how to install it and inferring it, and showing the correctness of using this method linguistically or not, as for the indication of the prohibition in terms of its types, and whether leaving is a duty or desirable, when and how is it due to the context in which it was mentioned and what it contains in this context of previous and subsequent. It is a style of many roses in the language to intend, and it is important among the addressees. That is why we have devoted our research to studying this method and clarifying its aspects and implications in a linguistic context, which is the Holy Qur’an, which we called (which is forbidden in Surat Al-Hujurat, a semantic grammatical study) because of this Surah in the context of divine teaching indications of how to deal with and address the Prophet as well as social matters, organization of the nation, and equality between Creation only piety. The research included an introduction showing the methodology of the study, then a prelude to the definition of the prohibition and its grammatical provisions and types, and highlighted the Surah Al-Hujurat and its provisions and the lessons learned from them, and this was followed by a semantic study of the terminology forbidden in Surah Al-Hujurat arranged according to their occurrence in the Surah, and the study concluded with the most important findings The study mechanism has results.